Morphological plasticity and ecophysiological response of ground ivy (Glechoma hederacea, Lamiaceae) in contrasting natural habitats within its native range. (2nd January 2021) - Sipek, Mirjana; Perčin, Aleksandra; Zgorelec, Željka; Sajna, Nina
Abstract: Some species intrinsically have a high invasiveness capacity, shown by high phenotypic plasticity and rapid growth, enabling a wide distribution across their native habitats and successful invasion in the introduced range. For such species, information from native habitats is critically important. An example is Glechoma hederacea, native to Eurasia but introduced and widespread in the USA. Our main objective was to investigate variation in traits of native G. hederacea populations across contrasting habitats: open, forest edge and understory. Vegetation was sampled and the ecophysiological and morphological traits were measured with accompanying environmental parameters. Results showed that in native habitats environmental conditions cover wide gradients of light and soil moisture. Plants had the highest cover in nutrient-rich, shaded habitats, representing the optimal habitat, indicating shade tolerance of G. hederacea . Plants from forest understory exhibited strong similarities in investigated traits to plants from the forest edge, even though this was a drier, sunnier habitat. Plants from open, sunny habitats experienced stress as indicated by the quantum efficiency of PSII and significantly higher sexual reproduction. Results show that G. hederacea is moderately tolerant simultaneously to shade and drought, a characteristic that has been reported for numerous invasive species, while at the same time it shares some characteristics with weedy plants.